Correction of Poikylocytosis and Blood Biochemical Indicators in Acute Blood Loss - V. V. Moroz; I. S. Novoderzhkina; E. M. Antoshina; A. V. Afanasyev; I. A. Ryzhkov; Yu. V. Zarzhetsky (Общая реаниматология, 2015)
Objective: to provide a rationale for the use of perfluorane to correct erythrocyte morphological changes and blood biochemical indicators in acute blood loss.Material and methods. Experiments were carried out in outbred male rats weighing 250—300 g under nembutal anesthesia. Blood loss was induced by arterial blood exfusion until blood pressure (BP) reached 40 mm Hg, following which this BP level was maintained for 60 minutes. Then the amount of blood withdrawn was reinfused. Perfluorane was injected intraarterially at a dose of 3 ml/kg 45 min before the start of blood loss. On the following day arterial and venous blood samples were harvested. The values of metabolic parameters (acid-base balance (ABB), hemoglobin (Hb), packed cell volume (PCV), and blood biochemistry), the morphological characteristics of erythrocytes (the size of discocytes and the percentage of stomatocytes and echinocytes), and the levels of reticulocytes in peripheral blood were studied. Results. Perfluorane exerted a normalizing effect on the values of blood ABB. Twenty-four hours after blood loss and reinfusion, Group 1 (a non-perfluorane group; n=8) showed reductions in Hb, PCV, and serum iron as compared to Group 3 (intact animals; n=12). In Group 2 (a perfluorane group; n=10), these indicators were decreased to a lesser extent. In these time periods, hypercholesterolemia was less marked in Group 2 than in Group 1. In Group 2, the mean diameter of a discocyte was larger than that in the animals of the two other groups. Group 1 displayed as high as 32% increases in the count of echinocytes with their virtually complete absence in the intact animals. At the same time, the levels of echinocytes in Group 2 animals were similar to those in the intact animals. As compared to Group 3, Group 1 exhibited a 4.5-fold drop in the percentage of reticulocytes (р≤0.05) while Group 2 showed a 2.2-fold rise in this indicator (р≤0.05).Conclusion. The injection of perfluorane at a dose of 3 ml/kg body weight 45 min prior to blood loss causes an increase in the values of Hb, PCV, and serum iron and a reduction in total cholesterol. The administration of perfluorane